An unusual cause of gastrointestinal bleeding and intestinal obstruction - Arena, Rosario; Gasperoni, Stefano; Lisotti, Andrea; Petrini, Chiara A. A.; Brancaccio, Mario L.; Triossi, Omero; Mussetto, Alessandro (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Arena R, Gasperoni S, Lisotti A, et al. An unusual cause of gastrointestinal bleeding and intestinal obstruction. Turk J Gastroenterol 2018; 29: 365-6.